CO2 activation by ligand-free manganese hydrides in a parahydrogen matrix. Issue 18 (3rd February 2021) - Huang, Tengfei; Yu, Wenjie; Cheng, Juanjuan; Cong, Fei; Xu, Bing; Wang, Xuefeng
Abstract : The reaction of MnH2 with CO2 gave insertion product HMn(η 2 -O2 CH) by concerted hydride ion transfer. Abstract : Manganese formate complexes, HMn(η 2 -O2 CH) and Mn(η 2 -O2 CH), are formed through MnH2 and MnH reactions with CO2 in solid parahydrogen and identified by matrix infrared spectroscopy with the basis of isotopic substitutions and theoretical frequency calculations. The reaction mechanism has been proposed that the reaction proceeds by concerted hydride ion transfer.